Effectiveness and Safety of Acupuncture to Treat Sleep Difficulties in Women on Hormone Replacement Therapy for the Treatment of Breast Cancer: A Randomized Controlled Trial - Mazzotti, Eva; Jacoangeli, Fabrizio; Sebastiani, Claudia; Scoppola, Alessandro; Cerutti, Massimo; Castellucci, Patrizia; Menichelli, Franco; Marchetti, Paolo (Advances in Social Sciences Research Journal, 2022)
Sleep difficulties are commonly reported by cancer patients as consequences of cancer or its treatments. Aim of this study was to measure the effectiveness and safety of acupuncture to treat sleep difficulties in breast cancer women on hormone replacement therapy. Methods: 58 breast cancer women were randomized to once weekly acupuncture session for 8 weeks (acupuncture group) or to a standard care session once a week, for 8 weeks (control group). The primary endpoint was change in sleep difficulties and insomnia, as measured by the Insomnia Severity Index (ISI), administered at baseline and 8 weeks later. Results: Random assignment produced equivalent groups regarding demographic and clinical characteristics at baseline. After 8 weeks, the changes in sleep quality and quantity were significantly different in the two groups. In the acupuncture group 43.33% go into complete remission (absence of insomnia), but none in the control group, and the mean ISI score decreased from 15.87 (standard deviation, SD= 3.95) to 9.80 (SD= 6.22), in the acupuncture group versus 17.46 to 15.39. No patient reported any problems or discomfort associated with acupuncture. Conclusion: A weekly session of acupuncture may have beneficial effects on quality and quantity of sleep among breast cancer women on hormone replacement therapy, after 8 weeks. The results could have important implications for Public Health to prioritize promotion of healthy sleep and acupuncture may be considered as alternative intervention in healthcare setting to ameliorate cancer patients’ sleep and quality of life.